Clinical relevance and implementation into daily practice of pharmacist-prescribed medication for the management of minor ailments - Amador-Fernández, Noelia; Botnaru, Irina; Allemann, Samuel Sebastian; Kälin, Véronique; Berger, Jérôme (Frontiers in Pharmacology, 2024)
Background Autonomous pharmacist prescribing was legally introduced in Switzerland in 2019 with the reclassification from prescription medication of 105 medications. Its aim was to limit medical consultations and healthcare costs. Objectives To evaluate the clinical relevance of the pharmacy prescribing medications compared to the over-the-counter medications (OTCs) and to evaluate its implementation into daily practice. Methods A comparison was undertaken by clinical pharmacists to evaluate chemical and galenical equivalences between pharmacy prescribing medications and OTCs using compendium.ch and pharmavista.ch. Then, a scoping review was carried out in October 2021 to determine clinical relevance according to clinical guidelines’ recommendations. Clinical relevance was completed by determining if pharmacy prescribing medications were part of a homogeneous therapeutic class (no differences in efficacy and safety considered in clinical guidelines, but rather inter-molecular differences) that included an OTC medication. To identify the most clinically relevant pharmacy prescribing medications, first-line treatments were considered. The implementation into daily practice in Swiss community pharmacies was evaluated through an online questionnaire. It included 15 questions divided in: pharmacy demographics, experience on pharmacy prescribing, use of prescribing medications and opinion about the them. Results Of the 105 pharmacy prescribing medications, 20 (19.0%) were first-line treatments without OTC equivalences. Six of them were OTCs reclassified for safety reasons. Ten medications (9.5%) showed a negative clinical relevance (they weren’t first-line therapeutic options to support pharmacist when managing patients or considered as to be avoided) compared to the OTCs available. For the questionnaire, 283 pharmacists from the German (40.3%), French (37.1%) and Italian-speaking regions (16.9%) answered. In the previous 6 months, 41.7% pharmacies had delivered 10-50 medications and 30.0% between 1-10 medications. In situations where patients could be equally treated with a pharmacy prescribing medication or OTC (with an identical OTC, similar OTC or an OTC for the same therapeutic group): 75.6%, 74.9% and 84.8% of pharmacists, respectively, would have chosen OTCs because it required less documentation and it didn’t require patients’ payment for the service. Conclusion Most pharmacist prescribing medications do not present clinical advantages compared to OTCs. In addition, other barriers for implementation were also pharmacists’ training and patient medications costs.